DISKURSUS HUKUM ISLAM DI INDONESIA TENTANG PERWALIAN PERKAWINAN ANAK ANGKAT - Fransisca Ismi Hidayah (Isti`dal : Jurnal Studi Hukum Islam, 2014)
This research is to answer the question, "Who is eligible to become a guardian for an adopted child marriage?" This issue is important given the differences between Islamic law (fiqh) and civil code. These differences often lead to confusion in the community. Adoption itself is usually set off from one issue to another issue. Therefor complexity of the marriage guardianship is inevitable, especially when it is viewed from the perspective of the two legal systems. Islamic law is expressly disclaim the conception of adopted children based on QS. Al-Ahzab [33]: 4 and5. State of adopted child is still a child of his biological father. As a result, law and arrangements of guardianship of adopted child marriage still follow his lineage, not the adoptive parents. Guardian of marriage is the biological father or brother of the father pathway (patrilinear). Guardianship of marriage is only for the bride. In other words, the civil code justifies the conception of the adopted child. Regarding the guardianship of marriage of adopted children, civil code set in article 331 of the Civil Code, Staatsblad 1917 No. 129, SEMA No. 2 In 1979, and SEMA No. 6 of 1983. Following the adoption, there are legal consequences arising, in terms of guardianship and inheritance. In the case of a guardianship, since the decision is made by the court, the adoptive parents become the guardian of his adopted son. Since that time, all the rights and obligations of the biological parents moved to the adoptive parents, except adopted children of muslim women.Keywordsguardianship of marriage, adopted child, fiqh, civil code. Tulisan ini hendak menjawab pertanyaan, ??Siapa yang berhak menjadi wali perkawinan bagi anak angkat?? Persoalan ini penting mengingat adanya perbedaan pandangan antara hukum Islam (fiqh) dan hukum perdata. Perbedaan ini kerapkali menimbulkan kebingungan di masyarakat. Pengangkatan anak sendiri biasanya berangkat dari persoalan satu ke persoalan yang lain. Kerumitan perwalian perkawinannya kemudian tidak bisa dihindari, apalagi jika ditinjau dari perspektif dua sistem hukum tersebut. Hukum Islam secara tegas menafikan konsepsi anak angkat berdasar QS. Al-Ahzab [33]: 4 dan5. Status anak angkat tetaplah anak ayah kandungnya. Akibatnya, hukum dan pengaturan perwalian perkawinan anak angkat tetap mengikuti nasabnya, bukan orang tua angkatnya. Wali perkawinan adalah ayah kandung atau saudara laki-laki dari jalur ayah (patrilinear). Perwalian perkawinan hanya diperuntukkan bagi mempelai perempuan. Sedangkan hukum perdata membenarkan konsepsi anak angkat. Mengenai perwalian perkawinan anak angkat, hukum perdata mengaturnya dalam pasal 331 KUHPerdata, Staatsblad 1917 No. 129, SEMA No. 2 Tahun 1979, dan SEMA No. 6 Tahun 1983. Setelah adanya pengangkatan anak, ada akibat hukum yang ditimbulkan, yakni dalam hal perwalian dan pewarisan. Dalam hal perwalian, sejak putusan diucapkan oleh Pengadilan, maka orang tua angkat menjadi wali dari anak angkatnya. Sejak saat itu pula, segala hak dan kewajiban orang tua kandung berpindah kepada orang tua angkat, kecuali bagi anak angkat perempuan yang beragama Islam.